Social costs of icatibant self-administration vs. health professional-administration in the treatment of hereditary angioedema in Spain - Blasco, Antonio J (Springer, 2013)
BACKGROUND: Icatibant is the only subcutaneous treatment for acute Type I and Type II hereditary angioedema with C1-esterase inhibitor deficiency (HAE-C1-INH) licensed for self-administration in Europe. AIM: To compare the economic impact of two icatibant administration strategies: health professional-administration only (strategy 1) versus including the patient self-administration option (strategy 2). METHODS: Economic evaluation model based on the building of a decision tree. Both strategies are assumed to have equivalent effectiveness. The payer (Spanish National Health System) and the social perspectives were considered. All relevant cost-generating factors were taken into account. The time horizon was one year. Sources of information included scientific evidence, official data and experts’ opinion. A deterministic sensitivity analysis was carried out to quantify the underlying uncertainty in the model. RESULTS: From the social perspective, which considers both direct (health care costs) and indirect costs (productivity losses), strategy 2 would result into average savings of €121.30 per acute attack compared to strategy 1. For Spain, this would achieve in an annual savings of €551,371. The reduction in direct costs accounts for 74% of the savings and lower indirect costs account for the remaining 26%. Savings per acute attack may range from €79.50 to €169.80; accordingly, the annual savings in Spain may vary between €90,319 and €2,315,360. CONCLUSION: Costs related to the management of acute HAE attacks with C1 inhibitor deficiency may be substantially reduced through interventions targeting home treatment by training patients to self-administer icatibant.